Genome organization and function in the cell nucleus - Rippe, Karsten (John Wiley & Sons, Incorporated, 2012)
By way of its clear and logical structure, as well as abundant highresolution illustrations, this is a systematic survey of the players and pathways that control genome function in the mammalian cell nucleus. As such, this handbook and reference ties together recently gained knowledge from a variety of scientific disciplines and approaches, dissecting all major genomic events: transcription, replication, repair, recombination and chromosome segregation. A special emphasis is put on transcriptional control, including genome-wide interactions and non-coding RNAs, chromatin structure, epigenetics and nuclear organization. With its focus on fundamental mechanisms and the associated biomolecules, this will remain essential reading for years to come.
Description based on publisher supplied metadata and other sources
Keywords: Electronic books; Aufsatzsammlung; Meiose; Mitose; Nucleolus; RNS; DNS; Nucleosom; Zellkern; Genom; Kernmatrix